IMPLEMENTASI THE THREE HORIZONS DALAM STRATEGI KINERJA KORPORASI BERKELANJUTAN DENGAN MENGANALISIS INTEGRASI BISNIS HOLDING DAN ANAK PERUSAHAAN PT. MORA TELEMATIKA INDONESIA - Ardin, Ryandi; Zulkifli; Miranda, Agustinus; Sihite, Mombang (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2022)
The purpose of this study is to determine the financial position of PT. Mora Telematika Indonesia with corporate benchmarking, Can implement the integration of the company's corporate strategy business lines at PT. Mora Telematika Indonesia so far, with regard to the goal of supporting sustainable competitive business performance, Can evaluate the company development strategy at PT Mora Telematika Indonesia so far, related to efforts to provide added value (added value) from the financial side for business strategy development and Can identify the company's strategic planning, towards competitive business performance in a sustainable manner at PT Mora Telematika Indonesia. This research uses a descriptive case study method. The data collected in this study is the financial report data of PT. Mora Telematika Indonesia, a subsidiary and benchmarking company. The results of this study are PT. Mora Telematics Indonesia and benchmarking companies are in a question mark position. In the subsidiary PT. Mora Telematics Indonesia, namely PT. West Palapa Ring, East Palapa Ring, PT. Oxygen Infrastructure and PT. Mora International Ltd is in a question mark position, while PT. Oxygen is at the dog's position. The results of the study of corporate strategy and the implementation of The Three Horizons in Holding and its subsidiary PT Mora Telematika Indonesia, will be able to provide optimal added value, namely the integration of business lines to be more and more effective in implementing the concept of development strategy with a growth strategy and Sustainable Company Performance . PT. Mora Telematika Indonesia and its respective subsidiaries must implement the concept of a growth strategy.